Adaptive fuzzy control for uncertain nonlinear systems subject to full state constraints and actuator faults - Su, Xiaohang; Philip Chen, C.L.; Liu, Zhi (Information sciences, 2021)
The paper investigates a theoretical and practical problem of handling a class of uncertain nonlinear systems carrying with full state constrains and actuators failure, where commonly occurs on marine vessel or aircraft. The knowledge of fuzzy logic systems (FLS), barrier Lyapunov functions (BLF) and backstepping technique are fusing to overcome this difficult issue. Fuzzy logic systems for approximating are used to allow more general of the considered systems, while the fuzzy compact set can be easily determined by preset constraints without any prior knowledge. Based on the fuzzy parametrization-like transformed systems, a novel backstepping control scheme is then proposed via constructing a series of barrier Lyapunov functions to finally ensure all the state constraints are not violated and compensate the possible actuator failures. It can be rigorously proved that all the closed-loop signals are globally bounded and the tracking error is guaranteed within a preserved compact set. Simulation results verify the established theoretical conclusion and show the effectiveness of the proposed scheme.